Problems of socio-economic development of Kazakhstan’s regions in the context of adaptation to the sustainable development - G. Khajieva; A. Omir (Экономика: стратегия и практика, 2020)
The article reveals the contradictory statement of the improving the regions of Kazakhstan to sustainable development, which consists in balancing three competing goals: a satisfaction the growing needs in the field of industrial development, to take into account the requirements of environmental safety and ensuring social protection of the population. The purpose of the research work is to identify the existing imbalances in the socio-economic development of the regions of Kazakhstan based on the analysis of macroeconomic indicators. The object of the adaptation of regions to sustainable development is the socio-economic potential of the region, the use of which is determined by the course of reforming the economy of the republic as a whole, the authors calculated the regional coefficient of adaptation to the sustainable development. Determining the degree of adaptation of regions to the requirements of sustainable development is one of the complex problems requiring combination of both quantitative and qualitative approaches. There were used statistical and comparative methods, which allows us to identify the areas of stability and instability, the boundaries of which are a “corridor” characterizing possible and permissible deviations from an unambiguous trajectory and choose the correct and necessary proportions between sectors. Based on the analysis, there were identified certain imbalances in the regional development of Kazakhstan. Thus, industrial regions are leading in many macroeconomic indicators, while outsider regions are ahead of them in the activity of small and medium-sized enterprises. Therefore, objective differences of the regions require differentiated approaches to developing strategies for their regional development. From this point of view, it seems necessary to identify clusters of problem regions where the solution of two interrelated problems, such as choosing a strategy to bring the economy to a competitive level and reducing differences in the development of social spheres, that means levelling the standard of living of the population should be implemented comprehensively.